Analysis of Research Trends in Library Services: : A Bibliometric Study Based on Scopus Data from 2020 to March 2025 - Nafisah Juliani; Wina Erwina; Asep Saeful Rohman (Department Library of Governance Institut of Home Affairs, 2026)
Background: Library services are a crucial element continuously adapting to the evolving information needs of the digital age, supporting the successful fulfillment of a library's vision and mission. Understanding current research trends in this field benefits researchers, librarians, and policymakers by helping to identify key topics and data-driven strategies for service development and policy formulation through relevant studies. Purpose: This study aims to analyze research trends in library services during the period from 2020 to March 2025, based on 842 publications retrieved from the Scopus database. Method: This study employed a bibliometric analys using Biblioshiny and VOSviewer to identify patterns in publication productivity, the most prolific countries, author collaborations, contributing institutions or organizations, leading sources of publication, and dominant phrases in the field of library services. Result: The findings indicate fluctuations in publication volume, with an increase observed from 2020 to 2021, followed by a significant decline from 2022 to March 2025. The United States, India, and Nigeria emerged as the most productive countries, demonstrating a relatively high level of international collaboration. Ajani, Yusuf Ayodeji was identified as the most prolific author. The majority of publications originated from journals focusing on library technology and media services, such as Library Philosophy and Practice. Institutions like the University of The Punjab were key contributors to library services publications, and a phrase analysis revealed that